Influencing factors of health utility values in older adult people with normal cognition or mild cognitive impairment: a cross-sectional survey - Du, Yanqiu; Zheng, Bingbing; Wang, Xiuru; Song, Tianlei; Liang, Di; Petersen, Jindong Ding; Huang, Jiayan (Frontiers in Public Health, 2025)
PurposeThe purpose of this study is to present the findings of a cross-sectional survey on health state utility (HSU) values, a crucial metric for economic evaluations, and to analyze the primary factors influencing the HSU values of individuals with normal cognition (NC) or mild cognitive impairment (MCI).MethodsA community-based survey was conducted in Haikou City, China, employing cluster random sampling to select participants. The presence of NC and MCI was determined through the administration of the Chinese version of the Mini-Mental State Examination (MMSE). The assessment of HSU was conducted using the Chinese version of the Short Form Six Dimensions version 2 (SF-6Dv2), in conjunction with a questionnaire that collected data on socio-demographic characteristics, health-related behaviors, and health conditions. The HSU values were calculated using the SF-6Dv2 value set, which was developed for the Chinese population. A multiple linear regression model was constructed to identify the factors influencing HSU values.ResultsThe survey indicated that 536 older individuals were identified with NC (mean age 70.7, SD 7.1, 51.4% females), 245 were identified with MCI (mean age 73.0, SD 7.8, 67.4% females). The mean HSU values in NC group and MCI group were 0.792 (SD: 0.174) and 0.720 (SD: 0.199), respectively. The optimal multiple regression model for the MCI group demonstrated a linear relationship between age, depression symptomatology, and MMSE score with HSU, with coefficients of −0.009 (p < 0.001) for age and −0.132 (p < 0.001) for depression symptomatology. And for NC group, the optimal multiple linear regression model included five variables: age, sex, monthly personal income, depression symptomatology, and number of comorbidities.ConclusionThis study presented findings on HSU and its influencing factors in both the NC and MCI groups. The older adult individuals with MCI demonstrated lower HSU compared to their cognitively normal counterparts. The results of the factor analysis indicated that intervention programs designed to enhance the health-related quality of life for older adult individuals with MCI should include strategies to address depression.